Endoscopic application of novel, infection‐free, advanced hemostatic material: Its usefulness to upper gastrointestinal oozing. Issue 1 (22nd August 2021) - Kubo, Yuto; Kobayashi, Satoru; Yamamoto, Keiichi; Nakagawa, Yoshie; Yamashita, Kotaro; Saito, Takuro; Tanaka, Koji; Makino, Tomoki; Yamamoto, Kazuyoshi; Takahashi, Tsuyoshi; Kurokawa, Yukinori; Yamasaki, Makoto; et al.
Abstract: Background: Self‐assembling peptides (TDMs) comprise synthetic amphipathic peptides that immediately react to changes in pH and/or inorganic salts to transform into a gelatinous state. The first generation of these peptides (TDM‐621) is currently used as a hemostatic agent in Europe. However, TDM‐621 exhibits slow gel‐formation and low retention capabilities on tissue surfaces. The second generation (TDM‐623) was therefore developed to encourage faster gel‐formation and better tissue‐sealing capabilities. Aim: The aim of this study was to verify the efficacy of TDM‐623 in terms of its hemostatic effect in endoscopic surgery. Materials and methods: Evaluation of the hemostatic effect in endoscopic surgery (animal study) was performed using eight porcine in spine position. Following systemic heparinization, we established a "bleeding model" by endoscopic grasping forceps on the anterior walls of the stomach and duodenum. In the hemostasis method, an endoscope with a distal hood was brought into contact with the bleeding point, and 1 ml TDM‐623 was applied to the wound. After TDM‐623 gelation, the endoscope was removed, and the acute hemostatic effect (after 2 min) was confirmed. Result: In the endoscopic bleeding model, 17 of the 23 cases (74%) showed complete hemostatic effects on the anterior wall of the stomach, and 18 of the 20 cases (80%) on the anterior wall of the duodenum, respectively. None of the applied gels were displaced from the anterior walls of the stomach and duodenum. Conclusion: The new self‐assembling peptide (TDM‐623) showed high hemostatic effects. TDM‐623 had potential usefulness for upper gastrointestinal endoscopic surgery.